ANALISA PENGARUH CURRENT RATIO, DEBT EQUITY RATIO, TOTAL ASSET TURNOVER RATIO, TOTAL SALES, WORKING CAPITAL TERHADAP PROFITABILITAS (Studi Kasus pada Perusahaan Kesehatan Subindustri Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Aisa Camalia Camalia; R. Djoko Sampurno (Faculty of Economics and Business Diponegoro University, 2022)
Previous research on profitability specifically discussing return on equity, especially in pharmaceutical subindustry health company listed on Indonesia Stock Exchange after the COVID-19 pandemic has not been widely studies by previous researchers. The object of this research is pharmaceutical subindustry health company listed on Indonesia Stock Exchange covering the periode 2016-2020. The sample used in this study amounted to 9 company. Multivariate linier regression were used to analyze the data with SPSS for windows version 23. This research based on 5 independent variable such as current ratio, debt equity ratio, total asset turnover ratio, total sales, net working capital and one dependent variable are profitability (return on equity). This result show each of liquidity (current ratio), company efficiency (total asset turnover ratio), firm size (total sales), working capital (net working capital) have positive significant with return on equity. Further leverage (debt equity ratio) show a positive but not significant with return on equity. Companies are expected to give more attention to the current ratio, total asset turnover ratio, total sales, net working capital because have significant positive effect on profitability. Meanwhile, for shareholders are expected to be a referce in making investment decision especially investing in the pharmaceutical industry in Indonesia. Further for the next research it is expect too add another variable outside of this study because the result of Adjusted R Square only 49,8% and the research period is longer so that the result are more representative of the profitability of pharmaceutical companies in Indonesia.